Fluorescent Particles Based on Aggregation-Induced Emission for Optical Diagnostics of the Central Nervous System - Shan Liu; Jinkuan Liu; Xue Li; Xiaoxin Du; Cheng Yin; Yong Luo; Chenzhong Li (Research)
In 2001, Tang’s team discovered a unique type of luminogens with substantial enhanced fluorescence upon aggregation and introduced the concept of “aggregation-induced emission (AIE)”. Unlike conventional fluorescent materials, AIE luminogens (AIEgens) emit weak or no fluorescence in solution but become highly fluorescent in aggregated or solid states, due to a mechanism known as restriction of intramolecular motions (RIM). Initially considered a purely inorganic chemical phenomenon, AIE was later applied in biomedicine to improve the sensitivity of immunoassays. Subsequently, AIE has been extensively explored in various biomedical applications, especially in cell imaging. Early studies achieved nonspecific cell imaging using nontargeted AIEgens, and later, specific cellular imaging was realized through the design of targeted AIEgens. These advancements have enabled the visualization of various biomacromolecules and intracellular organelles, providing valuable insights into cellular microenvironments and statuses. Neurological disorders affect over 3 billion people worldwide, highlighting the urgent need for advanced diagnostic and therapeutic tools. AIEgens offer promising opportunities for imaging the central nervous system (CNS), including nerve cells, neural tissues, and blood vessels. This review focuses on the application of AIEgens in CNS imaging, exploring their roles in the diagnosis of various neurological diseases. We will discuss the evolution and conclude with an outlook on the future challenges and opportunities for AIEgens in clinical diagnostics and therapeutics of CNS disorders.